Varagavank Monastery’s Khachkar Motifs: Understanding Production Through Parametric Methods - BAYER, SEMİH; Çakıcı Alp, Neşe (Birkhauser, 2023)
This study investigates the traditional religious architecture through the examination of Armenian Khachkar motifs at Varagavank Monastery in Van, Turkey. “Khachkar” is pivotal within Armenian religious architecture, denoting a minor architectural style and symbolising “cross-stone.” The study employs a parametric identification method to extract the fundamental unit of Khachkar motifs and develop a model to explore various variations. By utilising a mathematical analysis, the research showcases the practicality of this approach in facilitating diverse transformations within intricate designs. The study offers a comprehensive analysis of the built heritage found in Armenian religious architecture, enhancing the understanding and appreciation of these cultural artefacts. The findings of this study on Khachkars make valuable contributions to architectural research and deepen our comprehension of their significance in Armenian religious art.
Keywords: Armenian Khachkar Designs; Metamorphosis; Motif Generation; Parametric Modelling; Van Armenian Varagavank Monastery; Variation Control